Complementary and alternative therapies for epilepsy - Devinsky, Orrin; Schachter, Steven C.; Pacia, Steven, 1962- (Demos, 2005)
Annotation "Epilepsy is a difficult illness to control: up to 35% of patients do not respond fully to traditional medical treatments. For this reason, many people with epilepsy choose to rely on or incorporate complementary and alternative medicine (CAM) into their treatment regimens. Written for physicians and other professionals, as well as for knowledgeable laypersons, Complementary and Alternative Therapies for Epilepsy bridges the worlds of traditional medicine and CAM to foster a broader perspective of healthcare for patients."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.